HIV pretreatment drug resistance among cisgender MSM and transgender women from Lima, Peru. Issue 11 (27th November 2019) - Trebelcock, William L; Lama, Javier R; Duerr, Ann; Sanchez, Hugo; Cabello, Robinson; Gilada, Trupti; Segura, Patricia; Reisner, Sari L; Mayer, Kenneth H; Mullins, James; Bender Ignacio, Rachel A
Abstract: Introduction: Transmitted, or any pretreatment drug resistance (TDR, PDR) can compromise efficacy of first‐line antiretroviral therapy (ART). In Peru, genotypic resistance testing is not routinely performed before ART initiation, and estimated PDR prevalence prior to 2012 ranged from 1.0% to 4.7%. We aimed to update estimates of PDR prevalence in men who have sex with men (cis‐MSM) and transgender women (TW). Methods: We obtained HIV sequences from three studies of ART‐naïve cisgender‐MSM and TW (n = 470) in Lima, Peru from 2013 to 2017, almost two‐thirds of whom had acute or recent infections. Sanger sequences of HIV pol were interrogated for surveillance drug resistance mutations (SDRM) using the Stanford Calibrated Population Resistance (CPR) tool and scored for resistance to nucleoside reverse transcriptase inhibitors (NRTIs) and non‐nucleoside reverse transcriptase inhibitors (NNRTIs) with the HIVdb programme. We calculated binomial proportions and 95% confidence intervals. χ 2 and exact or trend tests were used to examine predictors of PDR. Results: Seventy‐seven (16.4%) individuals had PDR (95% CI: 13.2 to 20.0); most resistance was likely TDR since 63% were incident infections. SDRM were present in 9.8% (7.3 to 12.9). Resistance to any NRTI was present in <1% of individuals, while efavirenz resistance was present in 10% (6.9% to 12.4%). TW were not statistically more likely than cis‐MSM to have PDR (11.4% vs. 9.1%, p = 0.54). Age, incident versus prevalent infection, or residence district did not predict PDR. Prevalence of SDRM increased from 3% in 2013 to 21% 2017 within incident infections ( p = 0.04), but not when including prevalent infections. Conclusions: Prevalence of NNRTI resistance in three studies of ART‐naïve MSM and TW in Lima, Peru reaches 10%. Because our study reports PDR in a population in which most acquired HIV recently, the overall prevalence of PDR, including previously treated persons, is likely underestimated. These results underscore the need for a nationally representative survey of PDR in Peru and consideration of non‐NNRTI anchored first‐line ART options. This study also represents the first evaluation of PDR in cis‐MSM versus TW in South America, and demonstrates that, although TW are at higher risk of acquiring HIV, they are at similar risk of acquiring a virus with resistance mutations.